Oficina inclusiva de teatro educação para alunos com deficiência visual do ensino médio - NETO, Franklin José Carneiro (2020)
This text discusses the research carried out at the Inclusive Theater Education Workshop for Visually Impaired Students in public high schools, applied at the IFMA Santa Inês campus, in Santa Inês, MA, where the creation and implementation of a proposal was sought didactic-pedagogical that resulted in the inclusion of these students as theater practitioners. It was assumed that everyone can participate in an Education Theater Workshop and come to work, including people with Visual Disabilities, adapting to this the methodology used in the Conventional Theater Workshops. Accessibility laws are cited in order to demonstrate which paths of inclusion are intended in this work, while trying to clarify what is an Inclusive Theater Education Workshop. Dialogue was established with some authors such as Reverbel (1978, 1989, 2002), Koudela (1996, 2006), Barbosa (1975, 1997, 2002), Vygotsky (1991, 2001), Bruno (1993, 1997) and Slade (1978), among others, regarding the terms Theater and its relationship with Visually Impaired People. It registered the difficulties, possibilities and impediments for the participation of students with Visual Disabilities in the Proposed Activities and Games developed in the Inclusive Workshop, as well as what measures should be taken to have this inclusion adopted in other Theater Workshops. . The implementation of the Inclusive Workshop had its theoretical framework from the works of Boal (1977, 1996), Brecht (1967), Bruno (1997, 1993), Carvalho Salgado (2013), Mantoan (1998, 2015), Mazzota (2008, 2011 ), Spolin (1999, 2001, 2005), Stanislavski (1982, 1989,1995) and Vigata (2016). We used a qualitative approach, of an empirical and exploratory nature, through which we sought to analyze, through observation , the participation of 10 teenagers with Low Vision, high school students from public schools in Santa Inês, Maranhão, in the referred Workshop, their ability to act and participate in the processes of creating a theatrical carpentry that facilitates this performance, measuring errors and successes of this process. Through this research, the objective is to affirm the possibility of including the visually impaired in the entire artistic theatrical process, from acting to scenic creation, as well as contributing to their educational process as a whole and to their greater social inclusion.